استخدام بطاقة الأدء المتوازن في تقييم أداء مؤسسات التعليم العالي : دراسة تطبيقية على كلية التربية جامعة الملك خالد - البحيري، السيد السيد محمود (جامعة الملك خالد - كلية التربية - مركز البحوث التربوية, 2014)
هدفت الدراسة إلى استخدام بطاقة الأداء المتوازن في تقييم أداء مؤسسات التعليم العالي، ومحاولة تطبيقها في تقييم أداء كلية التربية جامعة الدلك خالد، وتوصلت الدراسة إلى إعداد رؤية مقترحة لتطبيق بطاقة الأداء المتوازن في تقييم أداء كلية التربية جامعة الدلك خالد، ومرت إعدادها بعدد من المراحل المرحلة الأولى: مرحلة إعداد بطاقة الأداء المتوازن، وتكونت هذه المرحلة من عدة خطوات هي: التخطيط وتقييم أوضاع المؤسسة )الكلية(، وتحديد رؤية المؤسسة، وترجمة الرؤية ورسالة الكلية إلى مجموعة من الأهداف، وخطوة تحديد الموضوعات الاستراتيجية، وخطوة رسم الخريطة، وخطوة تصميم بطاقة الأداء المتوازن. أما المرحلة الثانية فهي مرحلة التنفيذ والتي اشتملت على تنفيذ أبعاد بطاقة الأداء المتوازن الأربعة: بعد العملاء )المستفيدين(، وبعد العمليات الداخلية، وبعد التعلم والنمو بالإضافة إلى البعد المالي. أما المرحلة الثالثة فهي مرحلة المتابعة والتقييم. وفي نهاية الرؤية تم وضع عدد المعوقات التي من المتحمل أن تواجه تطبيق بطاقة الأداء المتوازن في تقييم الأداء المؤسسي لكلية التربية جامعة الدلك خالد ومقومات نجاحها، والجهات المسئولة عن نجاح عملية تطبيق بطاقة الأداء المتوازن في تقييم الأداء بكلية التربية جامعة الدلك خالد. وأخيراً أوصت الدراسة بأهمية دعم القيادات العليا داخل الجامعة لتطبيق الاتجاهات الحديثة في مجال تقييم الأداء المؤسسي ومنها بطاقة أداء المتوازن.
This study aimed to use the Balanced Scorecard in the evaluation of institutions of higher education performance, and try to apply in the performance of the College of Education, King Khalid University assessment, the study found to prepare a proposed plan for the implementation of the Balanced Scorecard in the performance of the College of Education, King Khalid University evaluation, and passed prepared a number of stages stage first: Prepare balanced Scorecard stage, and formed this stage, the number of steps are: planning and evaluation of the institution modes (college), and identify the organization's vision, and the translation of the vision and mission of the college to a set of goals, and step to identify the strategic issues, and step mapping, and step-performance card design balanced. The second stage implementation phase, which included the implementation of the four dimensions of performance balanced card: After clients (beneficiaries), and after internal processes, and learning and growth after addition to the financial dimension. The third phase is the stage of monitoring and evaluation. At the end of the plan has been developed by a number of obstacles that faced the Stoic application Balanced Scorecard corporate performance in the College of Education to evaluate the King Khalid University and the elements of success, and those responsible for the successful implementation of the Balanced Scorecard to evaluate the performance of the Faculty of Education, King Khalid University card process. Finally, the study recommended the importance of senior leadership support within the university to the application of modern trends in the field of corporate performance evaluation, including the balanced performance of the card
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- التعليم الجامعي -- طلاب الجامعات -- المؤسسات التعليمية -- التعليم العالي والبحث العلمي -- مستخلصات الأبحاث -- اللغات الأجنبية